2000
DOI: 10.1152/ajplung.2000.279.6.l1047
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of allergic inflammation in mice deficient in TNF receptors

Abstract: Tumor necrosis factor-alpha (TNF) is implicated as an important proinflammatory cytokine in asthma. We evaluated mice deficient in TNF receptor 1 (TNFR1) and TNFR2 [TNFR(-/-) mice] in a murine model of allergic inflammation and found that TNFR(-/-) mice had comparable or accentuated responses compared with wild-type [TNFR(+/+)] mice. The responses were consistent among multiple end points. Airway responsiveness after methacholine challenge and bronchoalveolar lavage (BAL) fluid leukocyte and eosinophil numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 54 publications
4
45
0
Order By: Relevance
“…A number of studies have previously suggested a role for TNF-α in the development of AHR (Gosset et al, 1991(Gosset et al, , 1992Williams et al, 2000;Coward et al, 2002;Aggarwal et al, 2003). In murine asthma models, a deficiency in TNF-α receptors has been determined to result in a marked attenuation of antigeninduced airway inflammation and AHR (Rudmann et al, 2000). Additionally, recent studies have shown that anti-TNF-α treatment administered to asthma patients resulted in a marked improvement in asthma symptoms, lung function, and AHR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have previously suggested a role for TNF-α in the development of AHR (Gosset et al, 1991(Gosset et al, , 1992Williams et al, 2000;Coward et al, 2002;Aggarwal et al, 2003). In murine asthma models, a deficiency in TNF-α receptors has been determined to result in a marked attenuation of antigeninduced airway inflammation and AHR (Rudmann et al, 2000). Additionally, recent studies have shown that anti-TNF-α treatment administered to asthma patients resulted in a marked improvement in asthma symptoms, lung function, and AHR.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that TNF-α, along with the Th2 cytokines, may critically contribute to several features of the response, antigen-induced inflammation and AHR, thus promoting allergic responses (Rudmann et al, 2000;Williams et al, 2000;Elias et al, 2003;Akdis et al, 2006;Eder et al, 2006;Umetsu et al, 2006). Furthermore, the release of leukotriene into the airspace as a consequence of the 5-LOX-mediated arachdonic acid pathway contributes to the release of airway mucus and the infiltration of inflammatory cells (Barnes et al, 1998).…”
Section: Ndga Inhibits Ova-induced Production Of Tnf-α and The Infiltmentioning
confidence: 99%
“…After weaning, female mice were exposed to aerosols of OVA 3% (w/v) (OVA grade V; Sigma-Aldrich) in PBS (pH 7.4) for 10 min on 3 consecutives days at 4, 8, and 12 wk of age. The aerosol exposure was performed within individual compartments of a mouse pie chamber (Braintree Scientific) using a Pari IS2 nebulizer (Sun Medical Supply) connected to an air compressor (PulmoAID; DeVilbiss) (24). The efficacy of the protocol in creating allergic airway disease in the female (future mother) mice was evaluated after each of the aerosolized allergen challenges at 4, 8, and 12 wk of age (23).…”
Section: Allergen Sensitization and Exposurementioning
confidence: 99%
“…After weaning, female mice were exposed to aerosols of allergen (3% (w/v) OVA (grade III, Sigma-Aldrich) in PBS, pH 7.4) for 10 min on 3 consecutive days at 4, 8, and 12 wk of age. The aerosol exposure was performed within individual compartments of a mouse pie chamber (Braintree Scientific, Braintree, MA) using a Pari IS2 nebulizer (Sun Medical Supply, Kansas City, KS) connected to air compressor (PulmoAID; DeVilbiss, Somerset, PA) (21). Immediately after the last aerosol exposure, the female mice were placed in cages with male mice to allow mating.…”
Section: Allergen Sensitization and Exposurementioning
confidence: 99%